2019
DOI: 10.1016/j.jclepro.2019.03.022
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective study of lignin-based and recycled carbon fibers in composites through meta-analysis of life cycle assessments

Abstract: Screening the life cycle assessment literature for information and recalculating extracted results was proven useful for identifying environmental challenges and opportunities in new, but related, contexts at early stages of technology development. The method was applied to carbon fiber reinforced polymers, a material of growing importance in industrial applications where a strong and/or light material is needed, such as in aircrafts and road vehicles. Many technology development efforts with the purpose of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…This stage contributes more than 65% and 70% to the climate change impact for the boat and the lever case, respectively, followed by the manufacture stage (approximately 30% for both studied cases). These results are in line with relevant work of the literature [ 92 , 93 , 94 ]. The reference EOL scenario has a minor contribution to climate change, mainly owing to the assumption that composite waste behaves as inert material in a landfill, thus a negligible contribution to methane emission is considered over the years [ 95 , 96 ].…”
Section: Resultssupporting
confidence: 93%
“…This stage contributes more than 65% and 70% to the climate change impact for the boat and the lever case, respectively, followed by the manufacture stage (approximately 30% for both studied cases). These results are in line with relevant work of the literature [ 92 , 93 , 94 ]. The reference EOL scenario has a minor contribution to climate change, mainly owing to the assumption that composite waste behaves as inert material in a landfill, thus a negligible contribution to methane emission is considered over the years [ 95 , 96 ].…”
Section: Resultssupporting
confidence: 93%
“…Therefore, there are inherent methodological problems in LCA when assessing its environmental performance, namely, how the environmental burdens of the system should be allocated to lignin and its co-products. It has previously been recognized that the choice of allocation approach in LCAs of lignin is crucial (Secchi et al 2019) because it can strongly affect the environmental performance of the end product, as was also shown for lignin-based carbon fibers by Hermansson et al (2019). However, lignin as a raw material for applications such as carbon fibers or adhesives are emerging technologies still in the development phase.…”
Section: Projects) In Such Technology Responsible Editor: Matthias Fmentioning
confidence: 99%
“…For example, Das (2011) uses mass-based allocation, Bernier et al (2013) compare emissions before and after lignin extraction was added to a mill, and Culbertson et al (2016) used system expansion by substitution as well as mass-based and economic allocation. During the work in a previous study on the potential environmental impact of lignin-based carbon fibers, it was found that the allocation method used for the lignin-generating processes could be of great importance for the resulting environmental impact of lignin (Hermansson et al (2019)). In that study, LCA results from different literature sources were explored, applying three different allocation methods to them (mass-based allocation, economic allocation, and a so-called consequential approach (in the present paper referred to as a marginal approach)).…”
Section: Projects) In Such Technology Responsible Editor: Matthias Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, studies have focused more on recycling CFRP waste due to its expensive price range and ability to retain maximum mechanical properties after recycling [7,143]. A recent study by Hermansson et al [144] suggested that, in the future, replacing polyacrylonitrile (PAN) with lignin as a raw material for CF will result in lowering the energy use and environmental impact at the time of recycling the waste CFRP.…”
Section: Life-cycle Analysismentioning
confidence: 99%